URGENSI DPR RI DALAM FUNGSI PENGAWASAN ANGGARAN DI INDONESIA - Babby Apriandani; Sumantri Sumantri; Sofian Sofian; Ahmad Ray Fadilah Sitompul (Smart Education, 2025)
Abstract: The role of the DPR (People's Representative Council) is important in building this country. Law No. 8 of 2012 concerning the Election of DPR Members, in which there is an explanation that the seats in it are 560 seats, which means that only 560 people can be in that place. The term of office of each DPR member is 5 years and ends simultaneously where the new DPR member takes his/her oath as a new DPR member with guidance from the Constitutional Court at a plenary session. In a simple sense, supervision can be interpreted as